2016
DOI: 10.1109/tmag.2015.2507169
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the magnetic polarizability tensor

Abstract: The aim of this paper is provide new insights into the properties of the rank 2 polarizability tensor } } M proposed in (P.D. Ledger and W.R.B. Lionheart Characterising the shape and material properties of hidden targets from magnetic induction data, IMA Journal of Applied Mathematics, doi: 10.1093/imamat/hxv015) for describing the perturbation in the magnetic field caused by the presence of a conducting object in the eddy current regime. In particular, we explore its connection with the magnetic polarizabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(107 citation statements)
references
References 38 publications
6
101
0
Order By: Relevance
“…Explicit formulae for the calculation of polarizability tensors have been found in a range of different electromagnetic applications. These include the leading order term in an expansion of the perturbed magnetic field ( H α − H 0 )( x ) as α →0 for a (multiply connected) permeable object with β 0 ( B )=1, β 1 ( B )≥0, β 2 ( B )≥0 in magnetostatics and expansions of ( H α − H 0 )( x ), and of the perturbed electric field ( E α − E 0 )( x ) as α →0 in electromagnetic scattering by simply connected dielectric, permeable, or conducting objects with β 0 ( B )=1, β 1 ( B )= β 2 ( B )=0 . In the aforementioned cases, scriptA=scriptTfalse(cfalse) is a suitably parameterised rank 2 Póyla‐Szegö tensor, and its coefficients can be computed by solving 3 scalar transmission problems or through the solution of 3 integral equations for given α , B , and material contrast c .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Explicit formulae for the calculation of polarizability tensors have been found in a range of different electromagnetic applications. These include the leading order term in an expansion of the perturbed magnetic field ( H α − H 0 )( x ) as α →0 for a (multiply connected) permeable object with β 0 ( B )=1, β 1 ( B )≥0, β 2 ( B )≥0 in magnetostatics and expansions of ( H α − H 0 )( x ), and of the perturbed electric field ( E α − E 0 )( x ) as α →0 in electromagnetic scattering by simply connected dielectric, permeable, or conducting objects with β 0 ( B )=1, β 1 ( B )= β 2 ( B )=0 . In the aforementioned cases, scriptA=scriptTfalse(cfalse) is a suitably parameterised rank 2 Póyla‐Szegö tensor, and its coefficients can be computed by solving 3 scalar transmission problems or through the solution of 3 integral equations for given α , B , and material contrast c .…”
Section: Introductionmentioning
confidence: 99%
“…This result also provides a solid mathematical footing for denoting truetrue-1ptscriptM1ptˇˇ as the rank 2 magnetic polarizability tensor (MPT), which the electrical engineering community predict for describing the characteristics of a conducting object in metal detection, eg, previous studies . In Ledger and Lionheart, we have obtained further results that relate the coefficients of truetrue-1ptscriptM1ptˇˇ to scriptTfalse(μfalse/μ0false) in the limiting case of ω →0, and, independent of the value of β 1 ( B ). For the limiting case of σ ∗ → ∞ , we have also shown that the coefficients of truetrue-1ptscriptM1ptˇˇ tend to those of scriptTfalse(0false) if β 1 ( B )=0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In applied mathematics and analysis, previous studies by [1,14,15,16,17,18,19] have shown that the perturbation due to the presence of the conducting objects can be represented by asymptotic formulas and PT is actually the dominant term in the formula. The asymptotic formula and the corresponding PT are generally not the same for different systems.…”
Section: Introductionmentioning
confidence: 99%
“…This will increase the chance of correctly identifying the target. Previous studies comparing the PT obtained by using explicit formula and field measurements were done by [5,18,24].…”
Section: Introductionmentioning
confidence: 99%